Analysis of the vitamin's list with pharmacoeconomic rates for the treatment of long covid conditions during the pandemic COVID-19 in Ukraine - Ya. O. Hrynkiv; O. B. Blavatska; G. Yu. Yatskova; O. M. Zaliska (The State Expert Center of the Ministry of Health of Ukraine, 2021)
To ensure adequate vital activity, especially during the COVID-19 pandemic, the human body needs, in particular vitamins, minerals (macro and micronutrients). The purpose of the study is the range, qualitative and quantitative composition of vitamin complexes (VC) in the pharmaceutical market of Ukraine; to develop a method of pharmacoeconomic analysis to determine the cost of treatment of VC. Materials of research - data DRLZ, «Compendium», prices for VC (www.tabletki.ua). Research methods: webometric, comparative, content, «cost minimization» analysis; systematization, generalization. 20 VCs were analyzed, of which 15 - group A11A (75%) and 5 - A11B (25%). The highest content of vitamins in: Elevit Pronatal, Vitrum Energy, etc. All groups of vitamins contain: Vitrum Centuri, Vitrum Energy. The least vitamins in - Metovitan, Optics. Vitrum Centuri and Vitrum Energy contain most of the trace elements. Metovitan, Optics, Quadevit contain the least amount of trace elements. In addition to trace elements, the composition of VC includes: amino acids (cysteine, methionine), papain, fish oil, etc. It is established that the recommended doses of vitamins A, C, B1, B2, B5, B6, B12 in Ukraine are higher than recommended by the WHO; D, B9, H - the recommended doses in Ukraine are lower than recommended by the WHO; recommended doses of all trace elements in Ukraine are higher than the WHO. 20 VCs are registered in Ukraine, of which 15 are group A11A and 5 are A11B. 90% of VC contain vitamins A, E, C, B1, B2, B9, B12, PP. Vitamin B6 - in 85% of VC; vitamin D3 is in the composition of 62% of VC; vitamin B5 - 58%; vitamins H and K - in the composition of almost 15% of VC. It was found that 54% of VCs contain calcium; 61.5% of VC contain iron and copper; 31% of VC contain phosphorus and manganese; up to 23% of VCs contain molybdenum, boron, nickel, vanadium, tin, etc. It is established that Zinc is a part of 62% of VCs registered in Ukraine. The results of pharmacoeconomic analysis by the method of «minimization of cost» showed that the affordability of domestic multivitamin and vitamin-mineral complexes are 1.5-4.7 times more economically affordable for treatment compared to imported, with a qualitative composition are similar. Quantitative content of vitamins and minerals in domestic VC meets the national requirements of daily intake.